MODERN METHODS OF SHAPING AND DEVELOPING LEADERSHIP QUALITIES AMONG FEMALE STUDENTS - Djabbarova Nilufar Bakhtiyarovna (Scholars Digest Publishing, 2025)
This article analyzes current approaches to cultivating leadership skills in female students based on recent pedagogical and psychological studies. It emphasizes several theoretical frameworks of leadership, such as personality characteristics theory and situational theories, demonstrating their evolution throughout time. The article explores the significance of psychological variables in cultivating leadership qualities, including self-awareness, social skills, motivation, and the ability for self-improvement.
Keywords: Leadership, female students, psychological research, pedagogy, transformational leadership, servant leadership, social skills, motivation.